Impact of various solid carriers and spray drying on pre/post compression properties of solid SNEDDS loaded with glimepiride: in vitro-ex vivo evaluation and cytotoxicity assessment. (3rd July 2018) - Rajesh, Sarvi Yadav; Singh, Sachin Kumar; Pandey, Narendra Kumar; Sharma, Parth; Bawa, Palak; Kumar, Bimlesh; Gulati, Monica; Jain, Subheet Kumar; Gowthamarajan, Kuppusamy; Singh, Saurabh
Abstract: Development of self-nanoemulsifying drug delivery systems (SNEDDS) of glimepiride is reported with the aim to achieve its oral delivery. Lauroglycol FCC, Tween-80, and ethanol were used as oil, surfactant, and co-surfactant, respectively as independent variables. The optimized composition of SNEDDS formulation (F1) was 10% v/v Lauroglycol FCC, 45% v/v Tween 80, 45% v/v ethanol, and 0.005% w/v glimepiride. Further, the optimized liquid SNEDDS were solidified through spray drying using various hydrophilic and hydrophobic carriers. Among the various carriers, Aerosil 200 was found to provide desirable flow, compression, dissolution, and diffusion. Both, liquid and solid-SNEDDS have shown release of more than 90% within 10 min. Results of permeation studies performed on Caco-2 cell showed that optimized SNEDDS exhibited 1.54 times higher drug permeation amount and 0.57 times lower drug excretion amount than that of market tablets at 4 hours ( p  < .01). Further, the cytotoxicity study performed on Caco-2 cell revealed that the cell viability was lower in SNEDDS (92.22% ± 4.18%) compared with the market tablets (95.54% ± 3.22%; p  > .05, i.e. 0.74). The formulation was found stable with temperature variation and freeze thaw cycles in terms of droplet size, zeta potential, drug precipitation and phase separation. Crystalline glimepiride was observed in amorphous state in solid SNEDDS when characterized through DSC, PXRD, and FT-IR studies. The study revealed successful formulation of SNEDDS for glimepiride.